Metformin Alleviates LPS-Induced Acute Lung Injury by Regulating the SIRT1/NF-κB/NLRP3 Pathway and Inhibiting Endothelial Cell Pyroptosis - Zhang, Yunqian; Zhang, Hui; Li, Siyuan; Huang, Kai; Jiang, Lai; Wang, Yan (Frontiers in Pharmacology, 2022)
Acute respiratory distress syndrome (ARDS), a devastating complication of numerous conditions, is often associated with high mortality. It is well known that endothelial cell (EC) damage and inflammation are vital processes in the pathogenesis of ARDS. Nevertheless, the mechanisms of EC damage are largely unknown. In the present study, we investigated the role of pyroptosis in the initiation of ARDS, and demonstrated that endothelial pyroptosis may play a pivotal role in the pathophysiology of ARDS. Metformin, an antidiabetic drug, exhibited a protective effect in lipopolysaccharide (LPS)-induced lung injury, and we hypothesized that metformin alleviated LPS-induced lung injury via inhibiting ECs pyroptosis. In vivo, male ICR mice were intratracheally injected with LPS, and metformin was previously administered intraperitoneally. Morphological properties of lung tissues were detected. We showed that metformin inhibited NLRP3 inflammasome activation and NLRP3-stimulated pyroptosis induction, as shown by decreased levels of cleaved caspase-1, N-terminal fragment of GSDMD, and protein contents of IL-1β in lung tissues of mice exposed to LPS. LPS-induced expression of vascular adhesion molecules was also reduced after the treatment with metformin. In vitro, exposure of pulmonary ECs to LPS resulted in increased expression of NLRP3 and pyroptosis-associated indicators. By inhibiting the expression of NLRP3 with NLRP3 inhibitor MCC950, pyroptosis-related markers and vascular adhesion molecules were ameliorated. Moreover, metformin treatment greatly inhibited the NF-κB signaling pathway and increased the expression of Sirtuin 1 (SIRT1) both in LPS-stimulated lung tissues and pulmonary ECs. Administration of the selective SIRT1 inhibitor nicotinamide significantly reversed the protective effect of metformin against endothelial pyroptosis and lung injury in LPS-treated ECs and LPS-induced acute lung injury (ALI). Thus, these findings demonstrated that metformin alleviated LPS-induced ALI by inhibiting NF-κB-NLRP3–mediated ECs pyroptosis, possibly by upregulating the expression of SIRT1.